A study of the level of professional image of future foreign language teachers in Ukrainian universities - Nenko, Y.; ORCID: http://orcid.org/0000-0001-7868-0155; Sytnik, T.; ORCID: http://orcid.org/0000-0002-0264-7196; Orlova, O. O.; Орлова, О. О.; ORCID: http://orcid.org/0000-0002-9956-9082 (Revista Brasileira de educacao do campo. – 2020. – Vol. 5, 2020)
У статті розглядається проблема розвитку професійного іміджу вчителя іноземної мови в Україні. Метою цього дослідження було з’ясувати ставлення студентів університетів України до досліджуваного поняття та виявити рівень його сформованості. Структура професійного іміджу майбутніх учителів іноземних мов складається з декількох основних конструкцій, які були описані в роботі: когнітивні, аксіологічні та операційні компоненти. Результати показують, що українські вчителі по-різному сприймають поняття професійного іміджу вчителя іноземних мов. Мета цього дослідження ‒ запропонувати організаційні, особисті та педагогічні умови для сприяння розвитку професійного іміджу майбутніх викладачів іноземних мов в українських вищих навчальних закладах.

The article addresses the problem of development of the professional image of a foreign language teacher in Ukraine. The present study was contemplated to ascertain the attitude of university students in Ukraine towards the studied notion and reveal the level of its formation. The structure of the professional image of future foreign language teachers consists of several underlying constructs which have been described in the paper: cognitive, axiological and operational components. Results show that Ukrainian teachers-to-be held different perceptions to the notion of professional image of a foreign language teacher. The purpose of this survey is to provide suggestion of organizational, personal and pedagogical conditions to facilitate the development of professional image of future foreign language teachers in Ukrainian higher education institutions.

В статье рассматривается проблема развития профессионального имиджа учителя иностранного языка в Украине. Настоящее исследование призвано выяснить отношение студентов вузов Украины к изучаемому понятию и выявить уровень его сформированности. Структура профессионального имиджа будущих учителей иностранного языка состоит из нескольких базовых конструктов, описанных в статье: когнитивного, аксиологического и операционального компонентов. Результаты показывают, что украинские будущие учителя по-разному воспринимают понятие профессионального имиджа учителя иностранного языка. Цель данного исследования ‒ предложить организационные, личностные и педагогические условия, способствующие развитию профессионального имиджа будущих учителей иностранных языков в украинских вузах.
Nenko, Yu. A study of the level of professional image of future foreign language teachers in Ukrainian universities / Yuliia Nenko, Tetiana Sytnik, Olena Orlova // Revista Brasileira de educacao do campo: brazilian journal of rural education. – 2020. – Vol. 5. – DOI: http://dx.doi.org/10.20873/uft.rbec.e10566.
Nenko, Y., Sytnik , T., & Orlova, O. (2020). A study of the level of professional image of future foreign language teachers in Ukrainian universities. Revista Brasileira De Educação Do Campo, 5, e10566. https://doi.org/10.20873/uft.rbec.e10566.
Nenko, Y., Sytnik, T., & Orlova, O. (2020). A study of the level of professional image of future foreign language teachers in Ukrainianuniversities. Rev. Bras. Educ. Camp., 5, e10566. http://dx.doi.org/10.20873/uft.rbec.e10566
NENKO, Y.; SYTNIK, T.; ORLOVA, O. A study of the level of professional image of future foreign language teachers in Ukrainianuniversities. Rev. Bras. Educ. Camp., Tocantinópolis, v. 5, e10566, 2020.http://dx.doi.org/10.20873/uft.rbec.e10566
Keywords: professional image; foreign language teacher; student; teacher’s professional image component; level; професійний імідж; викладач іноземних мов; студент; компонент професійного іміджу вчителя; рівень; профессиональный имидж; учитель иностранного языка; студент; составляющая профессионального имиджа учителя; уровень; Освіта. Педагогіка. Education. Pedagogy. Образование. Педагогика; Наукові публікації. Scientific publications. Научные публикации; publikatsii u WoS; Україна. Ukraine. Украина